PENGARUH PEMBELAJARAN TIPE FSLC TERHADAP HASIL BELAJAR SISWA - Elok Puspita Sari; Risdiana Chandra Dhewy; Intan Bigita Kusumawati (LPPM STKIP PGRI Sidoarjo, 2020)
This study aims to describe the effect type Formulate, Share, Listen and Create (FSLC) on student learning outcomes. The research method used is quantitative research. The design used in this study is One Shoot Case Study. The Sampling used by random sampling. This research was carried out at SMP Al-Islam Krian so that the sample was obtained in class VII A SMP Al-Islam Krian by applying rectangular material. The independent variable in this study was the administration of the FSLC type cooperative learning model. The dependent variable in this study is the learning outcomes of class VII A SMP Al-Islam Krian students. The instruments used in this study were observation sheets and test sheets. The test question sheet used in this study was in the form of 4 items for the description of the rectangular material. Validation in this study consisted of teacher and student observation sheets, test sheets, lesson plans (RPP). The results of data analysis used two stages, namely the classical assumption test and simple linear regression analysis. The results of the calculation of ttest at a significant level of 0,05 obtained by ttest ˃ ttable (3,764 ˃ 2,048) so that H0 is rejected. Thus the results of the hypothesis testing decisions partially indicate that there is the influence of the Formulate, Share, Listen and Create (FSLC) cooperative learning model on student learning outcomes significantly.